Place of ‘One Nation, One Election’ in the Contemporary Indian Electoral Reform Agenda: An Analytical Perspective: समकालीन भारतीय चुनाव सुधार एजेंडा में ‘एक राष्ट्र, एक चुनाव’ का स्थान: एक परीक्षणात्मक दृष्टि - Smita, Isha (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
‘One Nation, One Election’ is proposed as an important reform in India’s electoral system, with the aim of holding elections to the Lok Sabha and all State Legislative Assemblies simultaneously. Its primary objective is to reduce the administrative, economic, and political challenges arising from frequent elections, while ensuring continuity in governance and stability in policymaking. Under the current arrangement, repeated elections place a heavy financial burden, lead to misuse of administrative resources, and disrupt developmental activities due to the Model Code of Conduct. In addition, it encourages political polarization. Adopting the ‘One Nation, One Election’ policy would synchronize the terms of Parliament and State Assemblies, thereby reducing electoral costs and allowing governance to focus on development. However, there are several challenges in implementing this policy, such as the need for constitutional amendments, obtaining consensus among all political parties, and maintaining flexibility in the electoral process during unforeseen circumstances. Abstract in Hindi Language: ‘एक राष्ट्र, एक चुनाव’ भारत की चुनाव प्रणाली में एक महत्त्वपूर्ण सुधार के रूप में प्रस्तावित है, जिसका उद्देश्य लोकसभा और सभी राज्य विधानसभाओं के चुनाव एक साथ आयोजित करना है। इसका प्राथमिक लक्ष्य बार-बार होने वाले चुनावों से उत्पन्न होने वाली प्रशासनिक, आर्थिक और राजनीतिक चुनौतियों को कम करना है, साथ ही शासन में निरंतरता और नीति-निर्माण में स्थिरता सुनिश्चित करना है। वर्तमान व्यवस्था में बार-बार होने वाले चुनावों से भारी वित्तीय बोझ पड़ता है, प्रशासनिक संसाधनों का दुरुपयोग होता है, और आदर्श आचार संहिता के कारण विकास कार्यों में व्यवधान उत्पन्न होता है। इसके अतिरिक्त, यह राजनीतिक ध्रुवीकरण को भी बढ़ावा देता है। ‘एक राष्ट्र, एक चुनाव’ नीति अपनाने से संसदीय और विधानसभा कार्यकाल का समन्वय हो सकेगा, जिससे चुनावी लागत में कमी आएगी और शासन का ध्यान विकास पर केंद्रित रहेगा। हालांकि, इस नीति को लागू करने में कई चुनौतियाँ हैं, जैसे संवैधानिक संशोधनों की आवश्यकता, सभी राजनीतिक दलों की सहमति प्राप्त करना, और आकस्मिक परिस्थितियों में चुनाव प्रक्रिया में लचीलापन बनाए रखना। Keywords: चुनाव सुधार, एक राष्ट्र एक चुनाव, लोकतंत्र, राजनीतिक स्थिरता, संवैधानिक संशोधन, प्रशासनिक दक्षता।